2017
DOI: 10.1002/humu.23311
|View full text |Cite
|
Sign up to set email alerts
|

CNGB3 mutation spectrum including copy number variations in 552 achromatopsia patients

Abstract: Achromatopsia is a rare autosomal recessive cone disorder characterized by color vision defects, photophobia, nystagmus, and severely reduced visual acuity. The disease is caused by mutations in genes encoding crucial components of the cone phototransduction cascade (CNGA3, CNGB3, GNAT2, PDE6C, and PDE6H) or in ATF6, involved in the unfolded protein response. CNGB3 encoding the beta subunit of the cyclic nucleotide-gated ion channel in cone photoreceptors is the major achromatopsia gene. Here, we present a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 36 publications
3
51
0
3
Order By: Relevance
“…Yet a considerable number of cases remain genetically unsolved, in some cases because only a single pathogenic allele was identified for one of the known ACHM genes. We previously showed that copy number variations (CNVs) in CNGB3 contribute to these missing alleles in CNGB3 ‐linked ACHM (Mayer et al, ), but do not account for the second allele in all cases. From our entire ACHM cohort which comprises 1,100 independent families, we have selected 33 cases harboring a single disease‐causing variant in CNGB3 and in which CNV analysis failed to identify the second pathogenic allele.…”
Section: Introductionmentioning
confidence: 99%
“…Yet a considerable number of cases remain genetically unsolved, in some cases because only a single pathogenic allele was identified for one of the known ACHM genes. We previously showed that copy number variations (CNVs) in CNGB3 contribute to these missing alleles in CNGB3 ‐linked ACHM (Mayer et al, ), but do not account for the second allele in all cases. From our entire ACHM cohort which comprises 1,100 independent families, we have selected 33 cases harboring a single disease‐causing variant in CNGB3 and in which CNV analysis failed to identify the second pathogenic allele.…”
Section: Introductionmentioning
confidence: 99%
“…Both the GEDi testing and WES identified a single rare variant in the CNGB3 gene (c.1148delC, p.Thr383IlefsTer13) which has been reported to be pathogenic 6668 , but a second rare variant in CNGB3 was not identified, nor were other potential causative genetic variants forthcoming for the two affected members of the family. CNGB3 mutations are among the most common causes of cone dysfunction syndrome, but to the best of our knowledge, Chiari malformations have not been reported as an accompanying symptom in CNGB3 patients 69, 70 . Moreover, the 1.75e -3 gnomAD allele frequency of the p.Thr383IlefsTer13 variant is higher than expected for recessive pathogenic variants and two homozygous individuals are reported in the gnomAD database.…”
Section: Resultsmentioning
confidence: 75%
“…Missense mutations account for 4% of all human CNGB3 achromatopsia mutations, but there are currently no reported human cases of mutation at this residue. 11 The incidence of achromatopsia in the Pinegelap islander population is approximately 10% due to a CNGB3 missense mutation at a highly conserved residue: c.1304C>T; (p.S433F). The Cngb3 cpfl10 mouse model may provide a more appropriate preclinical model for developing genetic treatments for missense mutations in humans than the existing Cngb3 À/À (Cngb3 tm1Dgen ) mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…10 CNGB3 forms a heterotetramer cyclic nucleotide-gated (CNG) transmembrane channel with CNGA3 and is the most commonly affected gene in human achromatopsia. 11 CNGB3 is the minor component in direct channel conductance and plays a modulatory role. 12 In murine retinal sections, CNGB3 and CNGA3 colocalize and are expressed exclusively in cone photoreceptors.…”
mentioning
confidence: 99%